1995
DOI: 10.1126/science.7624794
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Bam HI Endonuclease Bound to DNA: Partial Folding and Unfolding on DNA Binding

Abstract: The crystal structure of restriction endonuclease Bam HI complexed to DNA has been determined at 2.2 angstrom resolution. The DNA binds in the cleft and retains a B-DNA type of conformation. The enzyme, however, undergoes a series of conformational changes, including rotation of subunits and folding of disordered regions. The most striking conformational change is the unraveling of carboxyl-terminal alpha helices to form partially disordered "arms." The arm from one subunit fits into the minor groove while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
251
0
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(265 citation statements)
references
References 34 publications
12
251
0
2
Order By: Relevance
“…The structures of the five type II endonucleases determined by x-ray diffraction, EcoRI (1), BamHI (2,3), EcoRV (4,5), PvuII (6,7) and Cfr10I (8), share substantial elements of similarity. Analysis of the enzymes complexed to DNA, where known, suggests a preliminary classification into two different groups (9).…”
mentioning
confidence: 99%
“…The structures of the five type II endonucleases determined by x-ray diffraction, EcoRI (1), BamHI (2,3), EcoRV (4,5), PvuII (6,7) and Cfr10I (8), share substantial elements of similarity. Analysis of the enzymes complexed to DNA, where known, suggests a preliminary classification into two different groups (9).…”
mentioning
confidence: 99%
“…In our structure, we observed that the inferred active site was more visible than in the structure of Dyda et al (15); however, we found that a surface loop (residues 141-148) was still disordered. In many wellstudied enzymes, flexible surface loops are important for substrate binding and catalysis (27)(28)(29), leading us to focus on the role of the region of residues 140-149. We substituted Gly residues at 140 and 149, potential hinges for the integrase flexible loop, with more constrained Ala residues and examined the mutant structures and enzymatic activities.…”
mentioning
confidence: 99%
“…The recent cocrystal structure of BamHI with a cognate oligodeoxynucleotide [7] is compatible with both mechanisms. As already described the catalytic centre is formed by three acidic residues because Glu-ll3 replaces the lysine residue found in the three other enzymes.…”
Section: Eeorimentioning
confidence: 68%
“…On the other hand, the known three dimensional structures of four restriction enzymes, namely EcoRI [2], EcoRV, PvulI [4,5], and BamHI [6,7], show striking homologies. The overall folds of EcoRI and BamHI as well as parts of the folds of EcoRV and PvulI are similar [8].…”
Section: Introductionmentioning
confidence: 99%